Handling counter-arguments in written argumentative discourse: implications for the teaching of English for academic purposes / May Siaw-Mei Liu and Jason Miin-Hwa Lim - May Siaw-Mei Liu; Jason Miin-Hwa Lim (Universiti Teknologi MARA Sabah, Kota Kinabalu, 2016)
While the ability to present a written argument convincingly is important for tertiary level students, research has shown that the written argument is one of the most difficult written genres for students to master. In this regard, many studies have been conducted on this genre and it was found that one of the moves which students encountered the most difficulty with was the move which handled counter-arguments. Novice writers have been known to avoid this particular move even though skilled arguers are expected to demonstrate an ability to raise counter-arguments and quash them strategically in order to strengthen a chosen claim. This study applied the robust two-layer move-step approach popularised by Swales (1990, 2004) to explore this particular move in argumentative essays. The qualitative analysis of this study included an examination of the linguistic features used by writers to communicate their intentions in this move and its subsequent steps. It was found that a move which handled counter-arguments might contain a combination of three steps and these were steps which raised a counter-argument, acknowledged the value of a counter-argument, and rejected a counter-argument. The findings of this study have pedagogical value because it can assist classroom practitioners in preparing teaching materials, particularly for a second language classroom at tertiary level.